Introduction to human nutrition - Lanham-New, S. (Susan); Hill, Thomas R. (Lecturer in nutrition); Gallagher, Alison; Vorster, H. H.; Nutrition Society (Great Britain) (Hoboken, NJ : Wiley, 2020)
"This textbook provides the scientific basis of nutrition in the context of systems and health approaches, exploring the core principles of nutrition and how these can be applied throughout training and practice: comprehensive in both its scope and approach, it has been fully updated by a global expert team to cover the most recent changes in the field; written by a team of internationally renowned experts; designed to meet the needs of students of nutrition worldwide"--
Introduction to Human Nutrition : A Global Perspective on Food and Nutrition / Professor Sue Lanham-New, Marcela Moraes Mendes -- Measuring Food Intake / Professor Una MacIntyre, Dr Friede Wenhold -- Food Composition / Professor Hettie Schonfeldt -- Dietary Reference Standards / Dr Kate Younger -- Body Composition / Professor Paul Deurenberg, Prof Dr Anja Bosy-Westphal, Prof Dr Manfred Muller -- Energy Metabolism / Dr Gareth Wallis -- Nutrition and Metabolism of Proteins and Amino Acids / Professor Joe Millward -- Digestion and Metabolism of Carbohydrates / Professor John Mathers -- Nutrition and Metabolism of Lipids / Professor Bruce Griffin -- The Vitamins / Professor David Bender -- Minerals and Trace Elements / Professor Sean Strain, Professor Kevin Cashman, Alison Yeates -- Phytochemicals / Professor Gary Williamson -- Physical Activity / Professor Alison Gallagher, Professor Marie Murphy, Dr Angela Carlin -- Nutrition Research Methodology / Professor J. Alfredo Martinez, Dr Estefania Toledo, Professor Miguel Martinez-Gonzalez -- Food Safety : A Public Health Issue of Growing Importance / Dr Catherine Burgess, Declan J. Bolton, Martin Danaher, Cristina Arroyo, Patrick J. O'Mahony and Lisa O' Connor -- Food and Nutrition - Policy and Regulatory Issues / Dr Aideen McKevitt, Jamie Gallagher Cassandra Ellis -- Food and Nutrition-Related Diseases : The Global Challenge / Dr Tom Hill, Professor Georg Lietz.
Includes bibliographical references and index.
english
Keywords: Nutritional Physiological Phenomena; Food